Enhancement of Methane Production in Anaerobic Digestion of Food Waste using Thermal Pretreatment - T.U. Habarakada Liyanage; Sandhya Babel (Environment and Natural Resources Journal, 2022)
Anaerobic digestion (AD) is an energy production process and food waste is a potential feedstock. The main biochemical reactions are Hydrolysis, Acidogenesis, Acetogenesis, and Methanogenesis. The hydrolysis step acts as the rate-limiting reaction and the pretreatment of the feedstocks can be used to support this step. In this research, thermal pretreatment was used as a potential method for food waste pretreatment. Six different pretreatment conditions were used: two different temperatures (80oC and 100oC) and three different pretreatment times (30, 60, and 90 min). The Bio-Methane Potential (BMP) test was conducted using 120 mL serum bottles for 20 days to determine the most suitable pretreatment conditions. An experiment was also conducted at the selected optimal conditions (80oC for 90 min) using a small-scale bioreactor against the control with a NaHCO3 buffer solution. The highest Soluble Chemical Oxygen Demand (SCOD) was observed at 100oC for 90 min. The optimal pretreatment was selected as 80oC for 90 min, which produced 14.75 mL/g VS of methane while the control produced 8.64 mL/g VS in BMP test. After a few days, the methane production started to slow down due to a decrease in pH. When a buffer was added, a specific methane yield of 120.13 mL/g VS was observed in the small-scale bioreactor. This was an 11.24% increase compared to the buffered control without thermal pretreatment. In conclusion, thermal pretreatment has a potential to enhance the AD but it is economical to use with less biodegradable waste than food waste.